Perspektif Hukum Islam (Hadd Al-Syurb) tentang Aia Niro dan Tuak (Khamr) di Nagari Batu Payuang Halaban: The Perspectives of Islamic Law (Hadd Al-Syurb) on Aia Niro and Tuak (Khamr) Activities in Nagari Batu Payuang Halaban - Salma Salma; Robi Revianda; Taufik Hidayat (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2020)
In Islamic law, khamr is a common type of alcoholic beverage that is forbidden for consumption due to its elements that can intoxicate and lead to loss of self-control. The government of Indonesia also forbids people from consuming the intoxicating beverage in certain levels. Nevertheless, a community group in Batu Payuang Halaban, Lima Puluh Kota Regency, West Sumatra Province, Indonesia, wherein their daily lives can be found a type of traditional beverage as same as khamr that is a fermented juice of sugar palm bunches. The people call it “tuak”. This research aims to investigate how the people of Nagari Batu Payuang produce aia niro and tuak, their motives for buying, selling, and consuming the drink, and judging it from the perspective of Islamic law (hadd al-syurb). This type of research is field research with a qualitative approach. Data sources consisted of primary and secondary. The data collection was conducted by observing the process of producing aia niro, tuak, and the transaction, and in-depth interviews with owners of sugar palm plantation, tuak producers, buyers, sellers, consumers, and local ulama (Islamic scholars). The data were analyzed in descriptive by reduction, display, and verification. To examine this research, the theory used was the concept of hadd al-syurb in Islamic law and the regulation on alcoholic beverages in Indonesia. The results show that aia niro is produced by extracting the bunches of male sugar palm and it is the raw material to produce tuak by leaving the aia niro in jerry cans and adding agarwood bark for 3 days. The sellers have various reasons to sell tuak and its raw materials. Besides the price is higher than brown sugar, it is also motivated by personal and other economic reasons as well as easier processing. People who drink tuak realize that it is intoxicating in a certain amount but they drink it to warm their bodies and relieve their fatigues. In the concept of hadd al-syurb, consuming tuak as an intoxicating substance is haram (forbidden) and is condemned to those who drink it. However, they who trade it are not punished by hudud since the Sunna proposition only refers to the transaction as an act of curse.